Pengaruh Profitabiltias, Ukuran Perusahaan Dan Likuiditas Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi - Refvisya Nur Ilhami; Listiorini Listiorini; Desi Desi (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
This study aims to determine the effect of profitability, firm size and dividend policy as moderating variables in manufacturing companies listed on the Indonesia Stock Exchange. This research is causal associative research and the type of data used is quantitative data. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange. Sampling using purposive sampling technique, so that the sample obtained as many as 32 companies with 5 years of observation. The analytical method used is Moderated Regression Analysis (MRA). The results of this study indicate that profitability has an effect on firm value, while firm size and liquidity have no effect on firm value. Dividend policy is able to moderate the effect of profitability on firm value, while dividend policy is not able to moderate the effect of firm size and liquidity on firm value.